Respuesta :

Answer:

[tex] \frac{4}{9} y - 7 = - 3[/tex]

• Add 7 to all sides:

[tex]( \frac{4}{9} y - 7) + 7 = - 3 + 7 \\ \\ \frac{4}{9} y = 4[/tex]

• multiply either sides by 9:

[tex]( \frac{4}{9} y) \times 9 = 4 \times 9 \\ \\ 4y = 36[/tex]

• divide either sides by 4:

[tex] \frac{4y}{4} = \frac{36}{4} \\ \\ { \underline{ \underline{ \: \: y = 9 \: \: }}}[/tex]

Answer:

[tex] \frac{4}{9}y - 7 = - 3 \\ \frac{4}{9} y = - 3 + 7 \\ \frac{4}{9}y = 4 \\ y = 4 \times \frac{4}{9} \\ cut \: 4 \: by \: 4 \\ y = 9 \: \: \: answer[/tex]

Step-by-step explanation:

please mark me brainliest